Avaliação do gerenciamento de perdas de água por vazamentos em municípios de médio porte - Santos, Erivelton Bortoli dos (2007)
The amount of water that is lost for leakage in Brazil discloses a scene with diametrical opposing extremities. On the other hand a significant of the population without supplying and the other exists part “more privileged” parcel that it even enjoys of the possibility of wastefulness, either for the inadequate use of this natural resources that also tend to the scarcity or for the recklessness and lack of interest of the operators who supply the service without the apparent concern in reducing or minimizing the index of losses, that has a national average that if it approaches to 40%. The information that the value of the index of losses is equal 40% is equivalent to say that for each liter of water produced and supplied to the consumers, almost another liter is not invoiced, maybe for imperfections of measurement (sub-measurement) and frauds in the hydrometer or for leakage in the net. With regard to the components of the index of loss, research made in diverse equipment indicates the average value of 8% to the hydrometer, being difficult esteem a value of the frauds. However, normally, excepting the cases of the clandestine linkings in slum quarters, superior values do not meet 1% for the frauds, what it leads to simply admit an average loss due to leakage reaching 31%. In this work it was looked to raise and to relate the actions managemental that has contributed for the success in the reduction of the index of losses, also promoting the maintenance in average values around 25%. The systems had been characterized in terms of infrastructure, existing measurements, management, and qualification of in charge staff it combat to the losses. Through experiences and comparison to the data of literature it was possible to identify practical, recommendable matter and technologies to the reduction of losses of water. The use of percentile indicators of each stage of the management was considered the use of a new indicator, called indicating generality of the management of loss of water (iggpa), where it is possible to evaluate the general conditions of operation of the system. The application of the considered indicators allows to the accomplishment of a diagnosis of the system with subsidies for the planning and implantation of a system of management of losses.